2014
DOI: 10.1161/circep.114.001671
|View full text |Cite
|
Sign up to set email alerts
|

REPLACE DARE (Death After Replacement Evaluation) Score

Abstract: Few studies have evaluated mortality and associated risk factors following CIED replacement or upgrade procedures. Advanced age, comorbid conditions, and procedure-related complications might contribute to mortality. The REPLACE Registry, a prospective multicenter study that evaluated patients undergoing device replacement with or without planned lead addition or revision, provided a unique opportunity to examine this question. 2 The objectives of the current © 2014 American Heart Association, Inc. Original Ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…The hazard ratio was 1.73 for each change of 1 DARE unit. These findings are consistent with those of Chung et al 1 First, there was a near-doubling of the risk score between nonsurvivors and survivors. Second, when adjusted for the REPLACE DARE score variables, none of the other predictors were retained, as the DARE score itself was uniquely selected with a forward stepwise approach (when using a backward elimination approach, however, renal function was also included in the regression model).…”
supporting
confidence: 92%
See 1 more Smart Citation
“…The hazard ratio was 1.73 for each change of 1 DARE unit. These findings are consistent with those of Chung et al 1 First, there was a near-doubling of the risk score between nonsurvivors and survivors. Second, when adjusted for the REPLACE DARE score variables, none of the other predictors were retained, as the DARE score itself was uniquely selected with a forward stepwise approach (when using a backward elimination approach, however, renal function was also included in the regression model).…”
supporting
confidence: 92%
“…We read with great interest the article by Chung et al 1 in which the authors used data from the prospective REPLACE Registry to develop a new score that may help identify patients with substantial mortality risk after cardiac implantable electric device replacement.…”
Section: Letter By Barra Et Al Regarding Article "Replace Dare (Deatmentioning
confidence: 99%
“…9 In this study, the authors have shown that in the REPLACE registry, comorbidities, but not complications, were associated with 6-month mortality after CIED replacement. On the basis of these findings, they have developed a mortality risk score, the REPLACE DARE Score, for identifying patients with limited expected longevity before the replacement, in whom the relative risk and benefit of the procedure should be carefully considered.…”
Section: Circ Arrhythm Electrophysiolmentioning
confidence: 68%
“…[102][103][104] Typically powered by lithium batteries, the devices must be replaced anywhere between five and ten years after the initial implantation. [105][106][107][108] This requires high-risk repeat invasive surgery, which increases hospital bills, increases the risk of failure or post-surgery complications, and reduces the quality of life of the patient. [109] The most feasible solution is to utilize an energy source that is both durable and flexible, accommodating the high demands of the human body.…”
Section: Tengs As a Power Source To Drive A Pacemakermentioning
confidence: 99%